Examining the effect of User Experience on Generation Y and Z Customers’ Satisfaction and Loyalty in Jago Syariah mobile banking - Rismawati, Rafifah; Irfany, Mohammad iqbal (IPB University, 2025)
The rapid expansion of internet access and the growth of Indonesia’s digital economy have accelerated the adoption of digital financial services, particularly mobile banking. In this increasingly competitive environment, Islamic digital banking providers face a dual challenge: ensuring Sharia compliance while delivering a seamless user experience (UX) that meets modern customer expectations. This study examines the effect of UX on Customer Satisfaction (CS) and Customer Loyalty (CL) among Generation Y and Z users of Jago Syariah mobile banking in Jabodetabek. A quantitative design was employed using an online survey (May–June 2025) with purposive sampling, yielding 203 valid responses from active users aged 17–44. UX was measured using the User Experience Questionnaire (UEQ) with six dimensions (attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty), while CS and CL were assessed using established indicators. Data were analyzed through descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The measurement model met validity and reliability criteria (AVE > 0.50; HTMT < 0.90; CR > 0.70). Structural results showed that UX positively and significantly influenced CS (β = 0.817; t = 21.176) and CL (β = 0.498; t = 6.716), and CS also positively affected CL (β = 0.443; t = 5.529), confirming the mediating role of satisfaction. The model explained 66.5% of variance in CS and 80.3% in CL. These findings highlight UX as a critical driver of satisfaction and loyalty in Islamic mobile banking, emphasizing the need for continuous improvements in usability, reliability, and feature performance to sustain customer retention and advocacy among digitally literate generations.